Gender Representation and Defaults in Lithuanian. Issue 1 (7th November 2019) - Adamson, Luke; Šereikaitė, Milena
Abstract : This study examines gender representation and defaults in Lithuanian by investigating the inflection on predicative adjectives (PAs). We provide novel evidence for two types of defaults in the representation of gender, masculine being the unmarked gender, and neuter being the absence of gender. It is demonstrated that neuter PAs appear when the subject lacks gender features accessible for agreement with the PA, which we refer to as non-agreement. In contrast, masculine PAs appear when the PA agrees with a subject bearing an unmarked gender feature. We analyze masculine and feminine as sharing a feature [GEND ] that originates on n, the locus of gender features (following Lecarme 2002 ; Lowenstamm 2008 ; Kramer 2015 ; 2016 ), with the default gender – the masculine – bearing only this feature, and the more marked gender – the feminine – having an additional feature [FEM ]. Neuter corresponds to the absence of these features. By placing gender features on the nominalizing head n, our account explicitly relates the distribution of gender inflection to nominal syntax and agreement.